Birth without intervention in women with severe mental illness: cohort study. Issue 2 (24th March 2022) - Taylor, Clare; Stewart, Robert; Gibson, Rod; Pasupathy, Dharmintra; Shetty, Hitesh; Howard, Louise
Abstract : Summary: The rate of normal birth outcomes (i.e. full-term births without intervention) for women with severe mental illness (SMI – psychotic and bipolar disorders) is not known. We examined rates of birth without intervention (spontaneous labour onset, spontaneous vaginal delivery without instruments, no episiotomy and no indication of pre- or post-delivery anaesthesia) in women with SMI (584 pregnancies) compared with a control population (70 942 pregnancies). Outcome ratios were calculated standardising for age. Women with SMI were less likely to have a birth without intervention (29.5%) relative to the control population (36.8%) (standardised outcome ratio 0.74, 95% CI 0.63–0.87).